In vitro antifungal activity of different components of Centratherum anthelminticum and Ocimum sanctum seed oils and their synergism against oral pathogenic fungi - Aparna H; Seshagiri; Sunil; Shashidara (Tabriz University of Medical Sciences, 2016)
Background. Opportunistic fungal infections like candidiasis are common in the oral cavity. In recent years Candida species have shown resistance against a number of synthetic drugs. This study assessed the antifungal activity of Centratherum anthelminticum and Ocimum sanctum seed oils against six common pathogenic Candidastrains. Synergistic activity of the major oil components was also studied. Methods. Antifungal activity of Centratherum anthelminticum and Ocimum sanctumseed oils were tested against six oral fungal pathogens, Candida albicans ATCC 90028, Candida krusei 6258, Candida tropicalis 13803, Candida parapsilosis22019, Candida glabrata 90030 and Candida dubliniensisMYA 646, by disc diffusion and broth microdilution methods to determine the diameter of inhibition zone (DIZ) and minimum inhibitory concentration (MIC), respectively. The oil was extracted using Soxhlet apparatus from seeds subjected to column chromatography (CC) and thin layer chromatography (TLC) and major components were separated and quantified. Results. All the six Candida strains showed growth inhibition to a variable degree when tested with both seed oils. Both seed oils showed antifungal activity. For Centratherum anthelminticum seed oil maximum DIZ at 7 μL was recorded at 75.7 mm for Candida albicans ATCC 90028, and the least DIZ was 45.7 mm for Candida dubliniensis MYA 646. For Ocimum sanctum seed oil maximum DIZ at 7 μL was 61.0 mm for Candida krusei ATCC 6258 and the least DIZ was 46.7 mm for Candida tropicalis ATCC 13803. The mixtures of phospholipids and unsaponifiable matter exhibitedMIC values at 1.25 μL for both oils, whereas neutral lipids fraction and unsaponifiable matter exhibited similar MIC at 2.5 μL against Candida albicans and Candida krusei. Conclusion. Centratherum anthelminticum and Ocimum sanctumseed oils exhibited strong antifungal activity against six different species of Candida and this may be attributed to various active components in the oil and their synergistic activity.